Effects of management and site history on plant succession and seedbank composition in old-fields at the UWM Field Station - (:unkn) unknown (My University, 1996)
Vegetation succession and seedbank composition were studied in eleven oldfields with differing crop histories. All the fields had been abandoned from agriculture in the mid-1960's, and some fields are currently receiving periodic management in the form of burning, mowing, and/or removal of exotic species. Oldfield plant composition was found to be most strongly influenced by management history since abandonment. Recently-managed fields had a greater abundance of certain early-successional nonnative species in the herbaceous layer, whereas unmanaged fields contained greater abundances of many later-successional, native perennial herb species. Woody plants showed the most significant response to management. Woody plant densities and species richness were significantly lower in recently-managed fields, whereas unmanaged fields had well-developed sapling and shrub layers. In contrast to the vegetation, the soil seedbanks contained many early-successional, non-native species irrespective of management history. In general, the management techniques are meeting the desired goals of maintaining diverse stages of successional vegetation and reducing establishment of invasive exotic shrubs.
Keywords: old field; abandoned agricultural field; seed bank; plant succession